The Relationship between Integrated Marketing Communication and Leadership Styles - In the Context of Malaysian Higher Education - Siti Aishah Chu Abdulllah; Mohamad Md Yussoff; Hasrina Mustafa (Universitas Kuningan, 2018)
The purposes of this study are to assess the level of IMC implementation, to investigate the factors for developing and implementing a successful IMC plan, and to determine the interconnection between leadership styles and IMC in the selected Malaysian public and private higher learning institutions (HLIs) based on the perceptions of administrators and lecturers. Qualitative methods were employed, whereby IMC four-stage framework and seven dimensions of full range leadership theory served as the basis of this study. The results of this study show that a majority of the interviewees claimed that their institutions have reached stage 4 (strategic integration) of the IMC framework. Nevertheless, there were inconsistencies in the answers between the administrators and lecturers. The results also reveal that the important factors in developing and implementing a successful IMC plan in Malaysian HLIs are uniting functional operations by aligning the activities of the HLIs toward serving the customers, getting support from the top management of HLIs, studying their customers thoroughly, and utilising social networks to communicate with their current and prospective customers. Moreover, the leadership styles practised in the interviewees’ institutions expose that the dimension of intellectual stimulation was the most mentioned, followed by laissez-faire, inspirational motivation, and management-by-exception. The leaders of the selected Malaysian public HLIs showed a higher tendency of practising transformational leadership style compared to the leaders of the selected Malaysian private HLIs who showed the tendency of practising transactional leadership style. Thus, practising an appropriate leadership style is an important factor that influences the effectiveness of leaders in the Malaysian HLIs. Keywords: Integrated marketing communication; integrated marketing communication framework; leadership styles; full range leadership theory.